Sensorineural Hearing Loss in Patients with Persistent Chronic Otitis Media in Terms of Duration and Type of Tympanic Membrane Perforation: SNHL with Persistent Chronic Otitis Media: Tympanic Membrane Perforation - Anis, Sharjeel; Abbas, Tahir Ghulam; Khan, Muhammad Moiz Ullah; Ali, Mujahid; Ahsan, Nadia; Iqbal, Muhammad (Pakistan Journal of Health Sciences, 2025)
The World Health Organization (WHO) estimated that worldwide, around 65-330 million people suffer from chronic otitis media, of which as high as 50 % suffer impairment in their hearing. Objectives: To determine the association between Sensorineural Hearing Loss (SNHL) in patients with chronic suppurative otitis media (CSOM) in terms of duration of CSOM and type of tympanic membrane perforation. Methods: This multicenter study was conducted at Hamdard University, Karachi, Fatima Jinnah Medical College, Lahore, and Loralai Medical College, Loralai, between March 2024 and February 2025, on patients diagnosed with active chronic otitis media. Patients with a history of meningitis, head trauma, tympano-mastoid surgery, congenital or acquired sudden hearing loss, or post-traumatic tympanic membrane perforation were excluded. Data were analyzed using SPSS version 23.0. Pearson correlation and one-way ANOVA were applied, with a p-value of less than 0.05 considered statistically significant. Results: Most patients were between 12 and 30 years of age. Mean duration of CSOM was 14.85 ± 9.1 months. The most common perforation of the tympanic membrane was marginal, in 204 (50.5%) patients. A significant moderate positive correlation was found between CSOM duration and SNHL (r=0.43, p=0.002). Patients with subtotal perforations (n=32) had the highest mean SNHL (37.1 ± 6.9 dB). The most frequent symptoms were ear discharge (88.1%) and hearing loss (94%). Conclusions: Both the duration of CSOM and the type of tympanic membrane perforation were significantly associated with sensorineural hearing loss. Prolonged disease, marginal perforations and subtotal perforations contributed to greater hearing loss, underscoring the need for early intervention.